Technological Challenges: A Case of Secondary-Level Mathematics Teachers’ Integrating ICT in Mathematics Classrooms - Adhikari, Ganesh Prasad (Academia Research Journal, 2024)
In Nepal, the integration of Information and Communication Technology (ICT) into mathematics teaching and learning has become a topic of growing interest and importance in the field of mathematics education. Nevertheless, the effective and efficient integration of technology into the classroom environment remains a significant challenge for mathematics teachers. Therefore, this study examines the technological challenges faced by mathematics teachers and the key factors that have the greatest impact on integrating ICT into teaching and learning activities in mathematics classrooms. An online survey design was used in the quantitative research. A structural online survey questionnaire was distributed through Viber, WhatsApp, and Messenger to 135 public and 150 private secondary-level mathematics teachers in Kathmandu Metropolitan City during the academic year 2023–2024. The overall response from mathematics teachers was only 197 (59.23%). The response data was downloaded into Excel and cleaned. Means, standard deviations, and multiple linear regression were used to analyze the cleaned data using the JAMOVI software. The data clearly show that there are no challenges in the use of ICT, professional development, and pedagogical issues. However, technological limitations present challenges from teachers’ perspectives. Additionally, technological limitations, professional development, and pedagogical issues have significant correlations and positive impacts on the use of ICT, with pedagogical issues emerging as the most influential factor. This means that teachers are qualified to integrate ICT into their teaching and learning activities. However, there were technological limitations in mathematics classrooms. Therefore, inadequate access to hardware, lack of technical support, and unreliable Internet connectivity are necessary for mathematics teachers to effectively incorporate ICT into their teaching and learning activities. Furthermore, further research should use a larger sample size to validate these results in diverse educational contexts in Nepal.